"Kansas to Oz” – An exploration of post-primary teachers’ knowledge of transition from primary to post-primary in Ireland - Murray, Una (School of Education, 2024)
This study focuses on the critical transition from primary to post-primary education from the perspective of post-primary in-service and pre-service teachers. The study aims to understand teachers’ knowledge and practices of transition, as well as the policy landscape in Ireland, as a way of offering a pathway for them to improve students’ experiences and performance as they progress from primary to post-primary. The exploratory sequential mixed methods study included interviews with post-primary students and teachers, principals and deputy principals, which informed an online national survey with 475 responses from post-primary teachers across all subject areas. Findings reveal new insights into teachers’ understanding of the concept of transition, exposing a gap between their idea of transition as a continuous process and their practical ‘fresh start’ approach in classrooms. Teachers’ roles in schools, and their age, are found to influence their understanding of primary education, while information transfer between schools in the form of the Education Passport faces dissemination challenges. The research used Galton et al.’s (1999) ‘Five Bridges of Transfer’ as the conceptual framework. However, the findings of the study indicated a disparity between the participants’ conceptualisation of transition as a process and the reality of a start from scratch approach in the post-primary subject classroom. Therefore, a new Action model for Transition called the ‘Three Ts of Transition’ emerged from this study. This new action model views transition as a process and highlights three aspects: Transition of Learning (ToL), Transition for Learning (TfL) and Transition as Learning (TaL). The model aims not only to bridge the gap between frameworks and theories, but also to provide a practical solution for educating teachers about transition and anchoring change in practice through a more reflective lens. Recommendations in the study include improving Education Passport format and dissemination; enhancing curriculum and pedagogical continuity through a New Framework for Action at a local level; promoting cross sector professional development nationally; and developing a framework guide to inform schools on transition policy formation.
Keywords: Transition / primary / post-primary / teachers / Bridges of Transfer / Three Ts of Transition Model